Clinicopathological Characteristics of Colorectal Cancer Patients with Different Mismatch Repair Statuses and Their Correlation with KRAS/NRAS/BRAF Gene Mutations - Jinchuan YU; Xuexue XIAO; Weiying HE; Yanan YANG; Junqiu YUE (Zhongliu Fangzhi Yanjiu)
ObjectiveTo investigate the clinicopathological characteristics of colorectal cancer patients with different mismatch repair (MMR) statuses and their correlation with KRAS/NRAF/BRAF (KNB) gene mutations. MethodsThe clinicopathological data of 477 patients with colorectal cancer were collected, and MMR, microsatellite instability (MSI), and KNB status were detected via immunohistochemistry (IHC), PCR–capillary electrophoresis, and next-generation sequencing (NGS), respectively. The clinicopathological features of patients with different MMR statuses and correlations with KNB mutations were analyzed. ResultsCompared with the patients in the pMMR group, the patients in the classical dMMR group were younger, included more females, and exhibited more tumors in the right colon, mostly mucinous adenocarcinoma and poorly differentiated tumors (all P<0.05). The tumors in the nonclassical dMMR group were commonly found in the right colon and were prone to special histologic types (all P<0.05). MLH1-PMS2 codeletion, BRAF mutation, and KRAS G13 codon mutation were common in patients in both the classical and the nonclassical dMMR groups (both P<0.05). The results of MMR IHC (100%) were highly consistent with those of MSI PCR (99.1%). Patients in the classical dMMR group with KRAS mutations were younger, included more males, and were prone to specific histologic types, but distant metastasis was rare (all P<0.05). Conversely, lymph node metastasis was rare in patients in the nonclassical dMMR group with KRAS mutations (P=0.005). The mutation rate of the MSH6 gene was relatively high in the nonclassical dMMR group (P=0.002), and all patients presented complete deletion of MLH1-PMS2 combined with nonclassical expression of MSH6 (100%). Five patients with medullary carcinoma components had complete deletions of MLH1-PMS2. Among the five patients, three had combined nonclassical expression of MSH2/MSH6. Two of the three patients carried the MSH6 gene c.3261 locus mutation. ConclusionThe clinicopathologic features of patients with classical/nonclassical dMMR colorectal cancer differ from those of patients with pMMR, and MMR IHC could be used to predict effectively the MSI status. The clinicopathologic features differ between classical and nonclassical dMMR colorectal cancer patients with KRAS mutations, but both groups present codeletion of MLH1-PMS2, BRAF mutation, and KRAS G13 codon mutation. In patients with nonclassical dMMR, complete deletion of MLH1-PMS2 combined with nonclassical expression of MSH6 is common. Mutations in the MSH6 gene may play a key role in the development of colorectal cancer with medullary carcinoma components.